As influências das TICS na aprendizagem infantojuvenil. - Brandão, Egislene Pereira de Sousa (Universidade Federal do Tocantins, 2020)
This Course Conclusion Paper deals with the influences of Information and Communication Technologies (ICTs) on child and adolescent learning, a theme present in everyday life and that needs to be inserted in the classroom, giving both teachers and students the opportunity to appropriate resources technological approaches to teaching. The main objective of this work is to understand if the use of technology facilitates the understanding of certain school contents, verifying if teachers use some technology in the classroom, what type of technology is most used, and, also to present students' conceptions about the use of ICTs in the teaching-learning process. For that, it was necessary to carry out a field research with some teachers and students of the fifth year of Elementary School of the Cristo Rei Parish School. It is believed that the data coming from the research can contribute to arouse interest in education professionals, mainly of teachers in using technological resources in the classroom. It is considered fundamental that all professionals of education can reflect on the practices developed in the classroom using technological resources that can contribute to student learning from the use of innovative and enriching methodologies by teachers.